Ferromagnetic resonance studies of exchange coupled ultrathin Py/Cr/Py trilayers - (:unkn) unknown (AMER INST PHYSICS, 2010)
Magnetic properties of ultrathin Py/Cr/Py trilayers have been investigated as a function of Cr spacer layer thickness by using ferromagnetic resonance (FMR) and vibrating sample magnetometer (VSM) techniques. The Cr spacer layer thickness was increased from 4 to 40 angstrom with 1 angstrom steps to determine the dependence of interlayer exchange coupling between ferromagnetic layers on the spacer layer thickness. Two strong and well resolved peaks were observed which correspond to a strong (acoustic) and weak (optic) modes of magnetization precession in the effective dc field due to the exciting external microwave field as the external dc field orientation comes close to the film normal. The separation of the two modes in the field axis depends on the thickness of Cr spacer layer. An interchange in the relative positions of the acoustic and optic modes has been observed for a particular thickness of Cr spacer layer as well. A computer program for magnetically exchange coupled N magnetic layers was written to simulate the experimental FMR spectra and to obtain the magnetic parameters of ultrathin Py/Cr/Py trilayers. FMR data have been analyzed from every aspect by using this program and interlayer exchange coupling constant was calculated for the prepared structures. It was found that the relative position of the peaks depends on the nature (sign) of the interlayer exchange coupling between ferromagnetic layers through Cr spacer layer. In Py/Cr/Py trilayers, strength of the interlayer exchange coupling constant oscillates and changes its sign with Cr spacer layer thickness with a period of about 11 angstrom. (C) 2010 American Institute of Physics. [doi:10.1063/1.3409020]
Keywords: LAYERED MAGNETIC-STRUCTURES; INTERLAYER EXCHANGE; GIANT MAGNETORESISTANCE; THIN-FILMS; FE LAYERS; FMR; OSCILLATIONS; TEMPERATURE; ANISOTROPY; MOMENTS